2001
DOI: 10.1007/s004200100241
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hand dermatitis in food industry apprentices: results of a 3-year follow-up cohort study

Abstract: Endogenous and exogenous factors contribute to the development of HD in bakers' and confectioners' apprentices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
2
11

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 14 publications
3
49
2
11
Order By: Relevance
“…The factor skin dryness (or itching body skin) as a risk of developing hand eczema may be linked to a genetic predisposition. These results are consistent with those of other occupational studies, which have shown that speciWc constitutional factors are accompanied by a signiWcant increase in the risk of the development of occupational eczema (Bauer et al 2001;Berndt et al 1999Berndt et al , 2000Uter et al 1999a, b).…”
Section: Potential Risk Factors For Skin Changessupporting
confidence: 93%
“…The factor skin dryness (or itching body skin) as a risk of developing hand eczema may be linked to a genetic predisposition. These results are consistent with those of other occupational studies, which have shown that speciWc constitutional factors are accompanied by a signiWcant increase in the risk of the development of occupational eczema (Bauer et al 2001;Berndt et al 1999Berndt et al , 2000Uter et al 1999a, b).…”
Section: Potential Risk Factors For Skin Changessupporting
confidence: 93%
“…In the healthcare workers the attributable risk was even higher and amounted to 37.4% 59) . ASD was also closely related to the development of skin problems during vocational training in hairdressing 66,67) , nursing 63) and food industry apprentices 68) , but not in trainee metal workers 56) . Loffler et al 69) showed that the risk of atopic health care employees (assessed by Diepgen score) to develop skin changes was especially high in the first 18 months of their training.…”
Section: Atopic Diathesis and Icdmentioning
confidence: 99%
“…Higher risk (1.5-fold) for OCD associated with respiratory atopy was also found in nurses 85) . However, the majority of studies have failed to find such associations 55,57,68,86,87) . Patients with respiratory atopy were found to have a similar barrier function and response to SLS induced irritation compared to healthy control subjects 88) .…”
Section: Atopic Diathesis and Acdmentioning
confidence: 99%
“…High loads of wet work, exposure to irritants and atopic skin diathesis have been reported to be the main risk factors for the development of OSDs [6,47]. We and others have shown that hand dermatitis seems to start early during apprenticeship [4,5,43,46], therefore preventive measures should be implemented early in vocational training at occupational schools and companies to achieve optimal efficacy [14,26,52].…”
mentioning
confidence: 96%